Transcriptomic miRNA and mRNA signatures in primary prostate cancer that are associated with lymph‐node invasion - Matias A. Bustos; Kelly K. Chong; Yoko Koh; SooMin Kim; Eleanor Ziarnik; Romela I. Ramos; Gianna Jimenez; David L. Krasne; Warren M. Allen; Timothy G. Wilson; Dave S. B. Hoon (Clinical and Translational Medicine)
Abstract Background Nomograms or comparable techniques can be used to determine which patients with prostate cancer (PCa) will benefit from extended pelvic lymph node dissection (ePLND). While nomograms help guide clinical decisions, ∼80% of the patients undergo unnecessary ePLND. This pilot study aims to identify both transcriptomic mRNA and microRNA (miR) signatures in primary PCa tumours that are associated with the presence of lymph node metastasis (LNM). Methods Primary PCa tumours obtained from 88 patients (pathologically diagnosed as N0 [pN0, n = 44] or as N1 [pN1, n = 44]) were profiled using two different probe‐based captured direct assays based on next‐generation sequencing and targeting 19398 mRNA transcripts (human transcriptome panel [HTP] dataset) and 2083 miRs (miRs whole‐transcriptome assay [WTA] dataset). The TCGA‐PRAD (pN0 [n = 382] and pN1 [n = 70]) and GSE220095 (pN0 [n = 138] and pN1 [n = 17]) datasets were used for validation using bioinformatic analyses. Results A four‐mRNA signature (CHRNA2, NPR3, VGLL3 and PAH) was found in primary tumour tissue samples from pN1 PCa patients, and then it was validated using the TCGA‐PRAD and GSE220095 datasets. Adding serum prostate‐specific antigen (PSA) values to the four‐gene signature increased the performance to identify pN1 (HTP [AUC = .8487, p = 2.18e‐09], TCGA‐PRAD [AUC = .7150, p = 8.66e‐08] and GSE220095 datasets [AUC = .8772, p = 4.09e‐07]). Paired miR analyses showed that eight miRs were significantly upregulated in primary PCa that were pN1 (p < .01). The eight‐miR signature performance increased when adding PSA (WTA dataset [AUC = .8626, p = 4.66e‐10]) or Grade group (WTA dataset [AUC = .8689, p = 2e‐10]). When combining the miR/mRNA signatures (miR‐663b, CHRNA2 and PAH) with PSA levels, it showed the best performance to distinguish pN1 from pN0 PCa patients. Conclusion This study found miR/mRNA signatures in primary PCa tumours that in combination with serum PSA levels may complement nomograms for better detection of PCa patients with LNM and triage patients into better surgical decision‐making. Key points Primary prostate cancer (PCa) tumours from patients pathologically diagnosed as N0 (pN0) or N1 (pN1) were dually assessed for microRNA (miRs) and mRNA levels using an NGS‐based assay. A four‐mRNA and an eight‐miRNA signature were found. The mRNA signatures were further validated using two datasets. The combination of serum prostate‐specific antigen (PSA) levels or Grade Group with the miR/mRNA signatures separates pN1 from pN0 PCa patients.